TRANSCRIPTION SITES IN SPREAD MEIOTIC PROPHASE CHROMOSOMES FROM MOUSE SPERMATOCYTES - Kierszenbaum, A. L. (The Rockefeller University Press, 1974)
Mouse spermatocytes at pachytene stage have been examined by whole-mount electron microscope techniques complemented with autoradiography as an approach for visualizing their transcriptive activity. Structural elements of meiotic bivalents, such as synaptonemal complexes and chromatin fibers, have been satisfactorily displayed in the total set of autosomal and sexual bivalents in single spermatocytes. Adequate preservation of the entire set of bivalents has provided a basis for recognition of sites where presumptive preribosomal RNA and heterogeneous nuclear RNA species are being transcribed at different segments of autosomal bivalents. Nucleoli attached to the basal knob region where nucleolar organizer cistrons are assumed to be located and ribonucleoprotein fibrils associated with distinct chromatin loops have been recognized. These structural findings have been correlated with display of [(3)H]uridine incorporation sites in thin-section and whole-mount electron microscopy autoradiographic preparations. A low transcriptive activity of the sexual bivalent contrasted with extensive gene expression in autosomal bivalents. Each sex chromosome shows a double axial core. A short region of pairing with a synaptonemal complex joins the two chromosomes at one end. We conclude that variations in the rate of RNA synthesis throughout meiotic prophase stages in the mouse are expressed as fluctuations in the amount and distribution of distinct RNA species at specific segments of the bivalents.